Conservative Aesthetic Management of White Demarcated Opacities Related to Molar‐Incisor Hypomineralization: A Four‐Year Follow‐Up Clinical Case - da Silva Júnior, Jefferson Pires; de Mendonça, Rafael Pinto [UNESP]; dos Santos Souza, Luana [UNESP]; de Moura Martins, Leandro; Bresciani, Eduardo [UNESP] (Wiley, 2025)
The objective of this study was to evaluate conservative approaches for the aesthetic management of a white demarcated opacity in molar-incisor hypomineralization (MIH). A 15-year-old female patient, accompanied by her legal guardian, presented to a public university postgraduate clinic reporting "discomfort with a white spot on her front tooth" (SIC). Clinical examination revealed a yellowish-brown discoloration on the vestibular surface of the maxillary central incisor. Clinical diagnosis via transillumination suggested a deep spot lesion resulting from MIH. The patient and guardian were presented with the following sequence of conservative treatments aimed at resolving the deep white spot lesion: microabrasion, dental bleaching, and resin infiltration. Following the partial enamel wear caused by microabrasion, a partial composite resin restoration was placed to cover the affected area. Annual clinical follow-ups were conducted over a four-year period, including clinical examination, photography, and transillumination of the treated area. No marginal degradation or restoration failure was observed during clinical evaluation, resulting in complete masking of the white spot lesion. The combined approach proved effective in masking the deep lesion, demonstrating the effectiveness of minimally invasive dentistry in challenging cases.